Pelatihan Perancangan Aplikasi Perhitungan Harga Pokok Dengan Microsoft Excel Bagi Anggota Dharma Wanita Bappeda Kota Mataram - Nina Karina Karim; Siti Atikah; Yusli Mariadi; Indria Puspitasari Lenap (Jurnal Gema Ngabdi, 2021)
Knowledge of business planning will help household businesses increase family income which in turn will make it easier to achieve common goals such as planning children's education, preparing pension funds, preparing pilgrimage funds and various other family needs. Some members of the Dharma Wanita Unit Bappeda Mataram City run household businesses such as food catering, handicrafts and buying and selling businesses. Not only planning the use of available financial resources in household businesses, this training aims to provide knowledge and ideas for members of the Dharma Wanita Unit Bappeda Mataram City regarding ways that can be applied to family businesses in calculating the cost of production of household businesses and increase family income through more appropriate business financial planning. By using simple functions in the Microsoft Excel program, service activity participants are trained to design simple applications that can be used to calculate the cost of production of household goods such as handicrafts, catering services and even retail.